He says, she says: gender and worklife - Hale, Mary (1999)
Comprehending and overcoming the resistance to equal employment opportunity outcomes requires not only having sufficient documentation and having "enough" women in the pipeline (both of which exist), but also an understanding of the interactions and "lived experiences" among men and women that perpetuates this resistance in organizations. This article explores these dynamics and relevant themes through conversations with men and women working in public organizations about how gender affects their workplace. In it, a communication model is proposed that is useful for diagnostics and intervention in organizations desiring to improve workplace relations and create a more equal workforce. - Reproduced
Keywords: Women